The Socio-Psychological Variables in the Meaning of Self-Consciousness and Movement Satisfaction of Physical Education and Sport Sciences Students - Amer Saeed Jassim1, Mustafa Jawad Mraidi2, Sanna Jabbar Gatea3, Saleh Chuaied Hilaiel4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This research aims at determine socio-psychological variables, self-consciousness and movement satisfaction of Physical Education and Sport Sciences students. Then, identify the relationship among the socio-psychological variable, self-consciousness and movement satisfaction of Physical Education and Sport Sciences students and predicting the socio-psychological variables in the meaning of self-consciousness and movement satisfaction of Physical Education and Sport Sciences students. In order to achieve the aims of the research, the researchers used the descriptive method by using the surveying method to recognize the variables of the research, the relationships between them and the predictions studies in order to find out how much self-consciousness and movement satisfaction contribute to the psychosocial variable. The community of the research made of Physical Education and Sport Sciences students/ University of Babylon / Fourth grade- morning classes, they were (140) students, the sample of the research made up of (15) students in order to represent the research sample by (11%), the researchers distributed the questionnaires for the research variables to the sample of the research, after analyzing and discussing the results they found out the following:1. Physical Education and Sport Sciences students enjoy high degrees in movement satisfaction, self-consciousness and the socio-psychological variables.2. The increasing of socio-psychological variables degrees has a relationship with the increasing of degrees in movement satisfaction, self-consciousness.3. There is an ability of predicting the psychosocial variables, depending on the reality of movement satisfaction, self-consciousness.